Impediments to wheat export from Ukraine - Iryna Kulyk; Thomas Herzfeld (System dynamics and innovation in food networks 2015, 2015)
According to prospects of international organisations like OECD and FAO, Ukraine will be one of the important suppliers of agricultural products on the world market in the coming decade. Thus, Ukrainian agricultural production and exports are important elements in sustaining global food security. However, the country threatens global food security as well as its own agricultural development when applying grain export restrictions, as happened several times in recent years. Therefore, any impediments to grain trade in the country should be carefully inspected. In this paper we analyse recent developments of Ukrainian agricultural policy influencing grain trade. We show that any export restriction brings large welfare losses compared to a free trade situation. We support our claim by a comparative analysis of the different export policies applied by the Ukrainian government on the domestic wheat market between 2006 and 2014. Additionally, we suggest and discuss alternative policy responses to realise the policy goal of domestic food security. As the policies applied, export tax, export quota and tax reimbursement, cannot be compared directly we quantify the tax equivalent of each trade policy measure. Under a set of specific assumptions the tax equivalent can be used to compare the effects of policies theoretically and empirically. Our findings go along with theory and show that export quotas in 2006 and in 2010 had a more restrictive effect on export than export taxes in 2011. Effects of non-reimbursement of VAT are very close to the effects of export tax in 2011 (at the level of 9%), mainly because most of the time these two measures were implemented simultaneously. We also calculated tariff equivalent of VAT non-reimbursement excluding the period of export taxes. Based on these results, the measure corresponds to a slight decline of the tariff equivalent in absolute terms. As an alternative policy option for the Ukrainian government to respond more efficiently to increasing world market prices in the future it is advised to use consumer-oriented measures for the most vulnerable groups of people instead of distorting market mechanisms.
Conference: 9th International European Forum on System Dynamics and Innovation in Food Networks
Keywords: 330; export restrictions; non-tariff barriers; Ukraine; wheat trade